2008
DOI: 10.1007/s11764-008-0054-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicted cardiovascular mortality and reported cardiovascular morbidity in testicular cancer survivors

Abstract: TC survivors should be followed regularly with respect to cardiovascular risk profile beyond the routine 10-year clinical follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 48 publications
(102 reference statements)
1
27
0
2
Order By: Relevance
“…Apartfromtumorrecurrence,follow-upschedulesshould include the detection of long-term side effects of chemotherapyandradiotherapy.Hypogonadism,metabolicsyndrome, andcardiovasculardiseaseaswellassecondarymalignancies arethemostimportantlong-termsequelae [15][16][17][18][19].Especially patientswhounderwentbothchemotherapyandradiotherapy haveanexcessiveriskforcardiovasculareventsorsecondary tumors [17].…”
Section: Introductionmentioning
confidence: 99%
“…Apartfromtumorrecurrence,follow-upschedulesshould include the detection of long-term side effects of chemotherapyandradiotherapy.Hypogonadism,metabolicsyndrome, andcardiovasculardiseaseaswellassecondarymalignancies arethemostimportantlong-termsequelae [15][16][17][18][19].Especially patientswhounderwentbothchemotherapyandradiotherapy haveanexcessiveriskforcardiovasculareventsorsecondary tumors [17].…”
Section: Introductionmentioning
confidence: 99%
“…A long-term follow-up in a large cohort of testicular cancer survivors showed that compared with healthy controls, cisplatin-treated patients had, at follow-up, increased systolic blood pressure, increased diastolic blood pressure and a higher prevalence of hypertension (18). In that cohort, patients in the high-dose cisplatin-treated group had increased odds for having intermediate/high risk in cardiovascular mortality, compared with the surgery group (OR=3.4, 95% CI: 1.3-8.7) (17). All of the above case reports led to the hypothesis that cisplatin may cause deleterious effects on the cardiovascular system.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, the vasomotor reactions have been reported to be related to plasma volume and to help maintaining cardiovascular homeostasis (13). Although in previous studies it was reported that cisplatin is associated with a higher incidence of cardiovascular mortality and morbility (17,18), the effect of cisplatin on vascular tone remains to be elucidated. Therefore, the aim of the present study was to evaluate the cardiovascular toxicity of cisplatin on the contractile function of rat thoracic aortas and to elucidate the possible underlying mechanisms.…”
Section: Introductionmentioning
confidence: 96%
“…The risk of the above long-term complications seems to be positively associated with the level of intensity of cancer treatment. [17][18][19] Whether the latter is caused by hypogonadism, which is more frequent in these patients as compared to the background population, is not yet known. However, low testosterone levels were reported as a marker of not only increased morbidity but also of mortality.…”
Section: Hypogonadism and Osteoporosismentioning
confidence: 98%
“…14,15 Nevertheless, in parallel with the increased incidence, a significant improvement in survival rates has been achieved and today, in the best centers, more than 95% of TGCC patients are cured. [17][18][19] Whether these diseases are fully or partially due to testosterone deficiency is so far unknown. However, there is no doubt that TGCC as such, as well as the therapy given, may constitute a hazard to reproductive function.…”
Section: Testicular Cancermentioning
confidence: 99%